Migration and Metamorphosis in Marie Ndiaye's Trois Femmes Puissantes - Deborah B. Gaensbauer (Studies in 20th & 21st Century Literature, 2014)
In her 2009 Goncourt-Prize-winning novel, Trois femmes puissantes (Three Strong Women), Marie Ndiaye experiments with a polyphonic, semi-fantastical rendering of identity-threatening displacements experienced by three women from different socio-geographic backgrounds. In a brief "Counterpoint" at the end of each of the novel's three sections--a narrative take on the musical technique employed by Ndiaye to introduce new focalizations and unexpected turns of events that complicate interpretations of the characters' behavior--each of the women is perceived as metamorphosed into a bird or a birdlike persona. This essay examines the innovative embedding of the shape-shifts in Trois femmes puissantes in both harrowing socio-political realities and the ambiguities of the fantastic and superstition to convey the dehumanizing, unequal power relations governing contemporary women's migration struggles.
Keywords: Marie Ndiaye; literary fantastic; women and migration; race and identity